Peningkatan Hasil Belajar Bahasa Indonesia Melalui Penerapan Model Pembelajaran Problem Based Learning (PBL) Siswa Kelas 3 SDN 7 Cakranegara Tahun Pelajaran 2022/2023 - Baiq Handayani Dwi Hartini; Mega Suci Yati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This study was motivated by the poor learning performance of SDN 7 Cakranegara grade III students in Indonesian language subjects. The purpose of this study is to determine the improvement in learning outcomes for this material using a learning-based learning (PBL) model. The objects of the study were third grade students. Data collection methods use observation, tests and documentation. This study consists of two cycles, with one learning event in each cycle. The data analysis technique uses quantitative analysis. The success criteria of the study set for student learning outcomes is 71 on a rating scale of 1 to 100. The results of the study show that the application of the PBL teaching model can improve student learning outcomes in Indonesian language subjects. Student learning outcomes, the focus of this study, improve with each cycle. The average learning result of students in the preliminary cycle reached only 26.66. After the introduction of the PBL learning model in the first cycle, the average value of the learning outcome increased to 74.80, and in the second cycle - to 81.46. Based on the above results, it can be concluded that the PBL teaching model influences the Discuss Indonesia learning outcomes of SDN 7 Cakranegara Grade III students.